2020
DOI: 10.3233/jad-200220
|View full text |Cite
|
Sign up to set email alerts
|

Tempe, Tofu, and Amyloid-β 1–40 Serum Levels in Ovariectomized Rats

Abstract: Estrogens have been found to reduce beta amyloid levels, a risk factor associated with dementia. We hypothesized that phytoestrogenic soybean products such as tempe and tofu might show similar effects. The aims of this study were to analyze the effect of tempe and tofu flour on beta amyloid1-40 serum levels in elderly rats. This research was conducted on female Sprague Dawley rats, aged 12 months. Before the intervention rats underwent ovariectomy (OVx) and were grouped into 5 intervention groups which were gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Researchers have found that consuming tempeh increases beneficial bacteria in the human intestinal tract [6, 7]. Correlations between tempeh consumption and brain function have also been observed in previous animal studies [8, 9]. Interestingly, Hogervorst et al [10] found that consumption of tofu (a non-fermented soy product) in older Indonesian adults has shown to increase risk of dementia and memory problems, although tempeh consumption seemed to offset this effect.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Researchers have found that consuming tempeh increases beneficial bacteria in the human intestinal tract [6, 7]. Correlations between tempeh consumption and brain function have also been observed in previous animal studies [8, 9]. Interestingly, Hogervorst et al [10] found that consumption of tofu (a non-fermented soy product) in older Indonesian adults has shown to increase risk of dementia and memory problems, although tempeh consumption seemed to offset this effect.…”
Section: Introductionmentioning
confidence: 78%
“…Second, tempeh supplementation modulates cognitive function through the change in Aβ level, which promotes neuron damage in Alzheimer-related processes. Kridawati et al [9] reported that tempeh and tofu flour supplementation in Sprague-Dawley rats reduced their Aβ level significantly at 2- and 5-week intervals, which is not found in the casein control group [10]. These previous studies also demonstrated that both supplementation of tempeh or the intended microbiota resulted in positive effect on cognitive function [10, 23, 25, 27].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…In a previous study, consumption of tempeh for 6 months was found to significantly increase cognitive function in the elderly population group with mild cognitive impairment (MCI) (Handajani et al, 2020). Animal studies found that the extract from tempeh can affect brain function through its role in the gastrointestinal system (Hamad et al, 2016;Kridawati et al, 2020). In a study comparing the administration of tempeh and soy milk for 28 days, Stephanie et al (2018) found that tempeh consumption modulated gut microbiota, increasing amounts of Bifidobacterium and A. muciniphila.…”
Section: Probiotics and Cognitive Functionmentioning
confidence: 99%